Surgery for severe thoracolumbar fracture dislocation via a posterior approach. Issue 12 (December 2015) - Feng, Zhang; Xiaoqing, Chen; Xiangdong, Chen; Junjie, Guan; Xingjie, Jiang; Yu, Yao; Ming, Li; Jian, Zhao; Yong, Cao
Abstract: Between June 2008 and June 2013, our department treated 16 severe thoracolumbar fracture dislocations (13 male and three female patients; mean age 33.6 years) with a pedicle screw system via an entirely posterior approach. We followed all patients for 18–69 months (mean 35 months). The mean operation time was 170 minutes (range: 120–280), and mean blood loss was 700 ml (range: 450–1300). The percentage displacement (mean ± standard deviation) improved from a preoperative value of 72 ± 20% to 10 ± 6% postoperatively, and the deformity angle (mean ± standard deviation) improved from 29.2 ± 15.0° to 12.6 ± 6.7°. Of the six patients with American Spinal Injury Association Grade A, one improved to Grade B, one to Grade C and four had little improvement. Of the five patients with Grade B, three improved to Grade C and two to Grade D. Of the four Grade C patients, two improved to Grade D, and the other two to Grade E. One Grade D patient improved to Grade E. No loosening or breakage of the internal implants occurred in the follow-up period. Therefore, we conclude that although it is difficult, the posterior approach alone is safe and biomechanically reliable for treating severe thoracolumbar fracture dislocations. The maintenance of deformity correction and stable local mechanical reconstruction in the follow-up period support this single approach strategy.